Big Data Analytics beyond the Single Datacenter. - Eugster, Patrick; Jayalath, Chamikara; Kogan, Kirill; Stephen, Julian (Computer (00189162), 2017)
Contrary to the notion that all big data can be processed in "the cloud," each cloud is tied to one or more datacenters, and cloud implementation details matter when data must be distributed over multiple centers. In these cases, approaches are needed to optimize the application's execution path.